T-grafting BODIPY-Based Photosensitizers: The Synthesis of 2,6-Diethylacrylic-8-(o-methoxyphenyl)BODIPY and Its DSSC Performance - Reinner Ishaq Lerrick; Wastiana Bere; Meliana Da Silva Braga; Agus Supriyanto; Ali Hashem Essa (Universitas Gadjah Mada, 2023)
A new T-grafting photosensitizer of Dye-Sensitized Solar Cell (DSSC) has been developed by aligning Donor-Acceptor (D-A) group in an axially chiral BODIPY. Synthesis of the dye was conducted over a linear approach involving one-pot, non-oxidative synthesis of 1,3,5,7-tetramethyl-8-(o-methoxyphenyl)BODIPY, bromination, and finally C2/C6 ethyl acrylate Pd-Heck coupling to produce 65% of 2-ethylacrylic-1,3,5,7-tetramethyl-8-(o-methoxyphenyl)BODIPY (BOD-8) and 35% of 2,6-diethylacrylic-1,3,5,7-tetramethyl-8-(o-methoxyphenyl)BODIPY (BOD-9), both characterized by the appearance of acrylic alkenes at 6.05, and 7.63 ppm for BOD-8, and the additional 5.43, 7.80 ppm doublet peaks for BOD-9. The resulting dye showed excellent photon harvesting-related photovoltaic properties and electronic injection and regeneration processes where the acrylic esters were found to be the Donor and the aryl was the Acceptor. Eventually, the dye produced a current at 0.5% efficiency, similar to the horizontal D-A DSSC photosensitizer design.